PERILAKU KONSUMTIF IBU RUMAH TANGGA (PERSPEKTIF SYARIAT ISLAM) - A. Sukmawati Assaad (Al-Amwal : Journal of Islamic Economic Law, 2017)
Indonesia's economic growth in the developed and developing carry capita income ofIndonesia's population also increased, causing living standards increasingly prosperouspopulation. It is affected by the person's shopping behavior patterns including housewives as afamily financial management, in addition to the shopping places are comfortable and provide allthe needs of consumers influence consumer behavior. In Islamic Sharia, one of the functionstreasure as jewelry, treasure the jewelry world are only temporary and for that reason, as aMuslim should be able to utilize the property as well as possible to worship Allah Swt